Comparative analysis of energy consumption, CO2 emissions and economic growth: evidence for OECD selected countries - Gmidene, Samia; zaidi, saida; Zouari Ghorbel, Sonia (International Journal of Accounting and Economics Studies, 2016)
The main purpose of this study is to investigate the causal relationship among renewable energy, nuclear energy consumption, economic growth, and CO2 emissions for selected OECD countries over the period 1980 to 2013. All variables are found to be cointgrated.Results of Granger causality show long-run relationship from GDP, renewable energy consumption and nuclear energy consumption to CO2 emissions, from CO2 emissions, GDP, to renewable energy consumption, from emissions, GDP to renewable energy, and from CO2 emissions GDP and nuclear energy consumption.In short run, results show that there exists bidirectional causality between GDP and CO2 emissions, and unidirectional causality running from renewable energy consumption to GDP. Also unidirectional causality running from renewable energy consumption to CO2 emissions without feedback but no causality running from nuclear energy consumption to CO2 emissions was found. This evidence suggests that renewable energy can help to mitigate CO2 emissions, but so far, nuclear energy consumption has not reached a level where it can CO2 emissions.
Keywords: Renewable Energy; Nuclear Energy; Economic Growth; CO2 Emissions; Granger Causality Test.